2019
DOI: 10.15632/jtam-pl/109602
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for the determination of Tesla turbine performance

Abstract: A numerical and experimental investigation of the Tesla turbine is presented in the paper. The experiment is conducted for various inlet pressure and load. The roughness of the rotor disc is determined as it is a key factor to obtain high turbine efficiency and power. The numerical investigations are performed for the same conditions as in the experiment. The computational results are compared with the analytical model. Comparison of performance characteristics show a relatively good agreement between the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This method is suitable for the same case study of the [43,44,45]. This correlation determines the equivalent sand roughness value ( ) using the roughness element height ( ).…”
Section: 29mentioning
confidence: 99%
“…This method is suitable for the same case study of the [43,44,45]. This correlation determines the equivalent sand roughness value ( ) using the roughness element height ( ).…”
Section: 29mentioning
confidence: 99%
“…The Tesla turbine differs from the conventional vane turbine in that it works by exploiting the boundary layer effect of the fluid: when the fluid flows around a solid wall and the motion is turbulent, the viscous forces are very small and negligible; however, the viscous forces are large in the thin layer close to the wall [13][14][15]. Due to this viscous force and the friction between the fluid and the disc makes a considerable velocity gradient along the wall in the normal direction, the thin layer near the wall is called the boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…Ciappi et al’s simulation results suggested that on a small scale and in miniature sizes, the Tesla turbine could be a valuable portable power generator [ 21 ]. Rusin et al modeled a five-disk Tesla rotor and the simulation showed a doubling of efficiency compared to normal bladed turbines [ 22 ]. However, there was a lack of research on Tesla turbines at the microfluidic scale until our group’s efforts in 2016 [ 23 ].…”
Section: Introductionmentioning
confidence: 99%